Are international capital flows coming to the end? - Różański, Jerzy (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
This article focus on present and future change in international capital flows in connection with basic tendencies in world economy (financial and economic crisis, autarkic tendencies, growing role of chosen countries, and collapse others), and problems of short or long life of the most famous theories connected with international capital flows. Therefore the two research problems were addressed: 1. As the literature related to foreign investments and international capital flows still presents theories explaining the origins of their occurrence and the conditions in world’s economy since the elaboration of these theories have significantly changed, the attempt to reconsider if the theories are still valid has been made. 2. Do the changes occurring in the global economy lead to reallocation of foreign investments, or rather to their disappearance? Accordingly, the basic assumptions of the most important theories explaining the reasons for making foreign investments has been presented, and subsequently, confronted with contemporary economic realities. Then, on the basis of available statistical data the direction of changes occurring in the value of international capital flows in the countries whose economic importance and share in these flows is relatively greatest has been determined.